(untitled) (Hematology Meeting Reports, 2009)
Lenalidomide is a thalidomidederivative that has shown clinical activity in multiple myeloma, myelodysplastic syndrome (del5q syndrome) and non-Hodgkin’s lymphomas. It belongs to a class of agents called immunomodulating drugs (IMiDs). In comparison to thalidomide, it is a more potent inhibitor of tumor necrosis factor alpha (TNF-a), while retaining some of its anti-angiogenic properties. Our group became interested in evaluating the therapeutic potential of lenalidomide in chronic lymphocytic leukemia (CLL) while searching for TNF-a and VEGF inhibitors. The rationale for targeting TNF-a and VEGF in CLL is based on our observation that patients with CLL have higher levels of TNF-a and VEGF-R2 than normal subjects and that high levels of these cytokines are associated with more aggressive disease and an inferior outcome.1,2